Nurse’s Work Climate and the Application of Patient Safety Measures in Sartika Asih Hospital, Bandung - Hayati, Suci Noor; Rusnandar, Siti Yuliani (KnE Life Sciences, 2021)
Patient safety is important and can be facilitated by improving the work climate for nurses. This study aims to describe the work climate of nurses and its impact on the application of patient safety at Sartika Asih Hospital, Bandung. The design of this study was descriptive with a cross-sectional approach. The population of this research is 84 nurses, and a simple random sampling technique was used to select 69 people. Data collection used the NWork Climate questionnaire by Suyanto with 36 statements. The univariate analysis used indicates that 56.5% respondents felt the work climate was not good, while 43.5%) felt it was good. According to Muadi (2019) work climate is a tool of environmental characteristics. Perceived directly by employees and assumed to have the main power in influencing employee behavior, the work climate is partially created visthe collaboration between the nurse and manager. The working climate of nurses in the hospital is still not good, so the hospital needs to make policies to improve this, including the scheduling of regular meetings and plans to increase the knowledge of nurses. Keywords: working climate; patient safety; nurse